Analisis Pembelajaran Daring Pada Mata Pelajaran IPS Selama Pandemi Covid 19 Di SMP Islamiyah Serua Kota Depok Tahun Ajaran 2020/2021 - Nasmal Hamda; Badrus Sholeh; Irawan Wisnu Kuncoro (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
The development of advance technology and information have an impact on teaching and learning process. In line with technological developments, at the beginning of 2020 the corona virus outbreak (Covid-19) had almost infected various countries. The impact caused by this epidemic has an influence on physchology and changes dramatically human behavior and in the long term. This pandemic has also changed the teaching system in Indonesia.Distance learning interactions are carried out by teachers and students. Islamiyah Junior High School (SMP) of Serua Depok City applies online for students. The purpose of this study is to analyze the online implementation of the Covid-19 pandemic at the Islamiyah Junior High School of Serua, Depok City. A descriptive method with a qualitative approach was used in in this study. The informants used were educators, school principals, and seventh grade students In integrated social studies subject.The Conclusion in this study indicated that the implementation of online learning in class VII runs effectively. This is shown by the consistency of education staff in directing and motivating students and parents as student companions in carrying out online learning activities carried out through the google classroom application, google meeting, zoom meeting, youtube and other social media. The use of this online based application is carried out by the teacher by uploading the material to be studied and providing an explanation of the material and the implementation of the tasks to be carried out by students.